22q11.2 Deletion Status and Disease Burden in Children and Adolescents With Tetralogy of Fallot. (February 2015) - Mercer-Rosa, Laura; Paridon, Stephen M.; Fogel, Mark A.; Rychik, Jack; Tanel, Ronn E.; Zhao, Huaqing; Zhang, Xuemei; Yang, Wei; Shults, Justine; Goldmuntz, Elizabeth
Abstract : Background—: Patients with repaired tetralogy of Fallot experience variable outcomes for reasons that are incompletely understood. We hypothesize that genetic variants contribute to this variability. We sought to investigate the association of 22q11.2 deletion status with clinical outcome in patients with repaired tetralogy of Fallot. Methods and Results—: We performed a cross-sectional study of tetralogy of Fallot subjects who were tested for 22q11.2 deletion, and underwent cardiac magnetic resonance, exercise stress test, and review of medical history. We studied 165 subjects (12.3±3.1 years), of which 30 (18%) had 22q11.2 deletion syndrome (22q11.2DS). Overall, by cardiac magnetic resonance the right ventricular ejection fraction was 60±8%, pulmonary regurgitant fraction was 34±17%, and right ventricular end-diastolic volume was 114±39 cc/m 2 . On exercise stress test, maximum oxygen consumption was 76±16% predicted. Despite comparable right ventricular function and pulmonary regurgitant fraction, on exercise stress test the 22q11.2DS had significantly lower percent predicted: forced vital capacity (61.5±16 versus 80.5±14; P <0.0001), maximum oxygen consumption (61±17 versus 80±12; P <0.0001), and work (64±18 versus 86±22, P =0.0002). Similarly, the 22q11.2DS experienced more hospitalizations (6.5 [5–10] versus 3 [2–5]; P <0.0001), saw more specialists (3.5 [2–9] versus 0 [0–12]; P <0.0001), and used ≥1 medications (67% versus 34%; P <0.001). Conclusions—: 22q11.2DS is associated with restrictive lung disease, worse aerobic capacity, and increased morbidity, and may explain some of the clinical variability seen in tetralogy of Fallot. These findings may provide avenues for intervention to improve outcomes, and should be re-evaluated longitudinally because these associations may become more pronounced with time.